Prophet Muhammad's Birthday: Inviting Students to Make Use of Their Free Time - Anggra Prima; Satriah; Ramdanil Mubarok (PT. Sharia Journal and Education Center, 2024)
The commemoration of the Prophet Muhammad's birthday is not only a spiritual momentum but also serves as a learning medium to shape student character, especially in time management and productivity. This community service program aims to integrate the Islamic values taught by the Prophet into students' lives through creative activities based on the Prophet's birthday. The implementation method uses a Participatory Action Research (PAR) approach, which involves students actively in problem identification, activity implementation, reflection, and evaluation. This activity was carried out at SMA Negeri 1 Sangatta Selatan, and it included various activities, such as inspirational lectures, creative competitions, and joint reflections. Results showed that students experienced increased understanding and motivation in using time productively. The post-activity survey noted changes in students' positive attitudes towards time management, contributing to their Islamic character building. This research contributes to the development of Islamic values-based character education approaches, particularly in addressing the challenges of young people in the digital era who often experience problems in time management.